Academic success: Is it just about the grades?. Issue 1 (1st January 2018) - Cachia, Moira; Lynam, Siobhan; Stock, Rosemary
Abstract: Researchers examining academic success often quantify it in terms of assessment grades. This assumption is questioned here by considering the students' understanding of academic success. The presented study aimed to identify students' views of its definition and the factors they perceive as crucial in attaining it. Sixteen undergraduate Psychology students at a modern university in London, United Kingdom took part in one of three focus groups. Participants defined academic success as: the accomplishment of the learning process; gaining subject knowledge; and developing employability skills. Thematic analysis of the collected data resulted in two themes: intrinsic factors, including motivation, self-directed learning and personal skills; and extrinsic factors, including teaching content and the student support structure. The discussion of these results at the conference led to the conclusion that achieving academic success and minimising skill gaps for employability post qualification requires the intrinsic elements to be addressed as an integral part of the compulsory programme rather than presented as optional add-ons.